Factors affecting supply chain collaboration in Thailand’s dairy industry: pilot study - VAJIRABHOGA, V.; SUTIWARTNARUEPUT, K.; PORNCHAIWISESKUL, P. (Utopía y Praxis Latinoamericana, 2021)
ABSTRACT 90% of milk producers are smallholders. In addition to disease control and health regulations, supporting milk producers in supply chain collaboration can play a major role in improving the success of the dairy industry. This pilot study aims to develop conceptual frameworks in 9 areas as follows: performance and commitment, processes, measurement and evaluation, strategies, internal and external communication, long-term business, operations, cost reduction, learning and knowledge, and 32 identified factors by exploratory factor analysis. The verified model will be able to give a clearer understanding of the factors affecting supply chain collaboration that impacts Thailand’s dairy industry. RESUMEN El 90% de los productores de leche son pequeños agricultores. Además del control de enfermedades y las regulaciones sanitarias, apoyar a los productores de leche en la colaboración de la cadena de suministro puede desempeñar un papel importante en la mejora del éxito de la industria láctea. Este estudio piloto tiene como objetivo desarrollar marcos conceptuales en 9 áreas de la siguiente manera: desempeño y compromiso, procesos, medición y evaluación, estrategias, comunicación interna y externa, negocios a largo plazo, operaciones, reducción de costos, aprendizaje y conocimiento y 32 factores identificados por el análisis de factores exploratorios. El modelo verificado podrá brindar una comprensión más clara de los factores que afectan la colaboración en la cadena de suministro y que impactan en la industria láctea de Tailandia.